Frugal innovations for the 'unserved' customer: An assessment of India's attractiveness as a lead Market for cost-effective products - Rajnish Tiwari; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2012)
This study builds on our previous work, which had questioned the validity of certain assumptions of the lead market theory in the face of changing ground realities in a globalized world. Sustained economic growth and proven technological capabilities in some emerging economies like China and India call for a reassessment of the appropriateness of the conventional wisdom that had held true until recently. While our previous study had re-built a theoretical background of the lead market model by introducing new elements, and doing away with certain others, with the help of two in-depth case studies; the purpose of the present study is to specifically assess India's potential as a lead market for cost-effective frugal innovations. The study crystallizes the inherent characteristics of frugal innovations, their development process and market success in the domestic and overseas markets by analyzing four successful product innovations from selected industries in India. The factors identified thus are then incorporated in the theoretic model to derive propositions about India's lead market potential. Whereas affordability and economies of scale have traditionally constituted the primary concern for frugal innovations, an increasing shift towards value proposition is identified. Intensifying competition and growing customer aspirations are changing the nature of frugal innovations. The hitherto unserved customer demands attractive designs and modern technologies to come out of his shell of non-consumption. Our research confirms that frugal innovations can benefit end-consumers and firms, simultaneously. Better-designed products also have positive impact on the lead market potential, creating a virtuous cycle. The study also discovered that the increasing need for sophistication coupled with continued cost pressures is shifting the product development processes into the domain of open global innovation, which also helps reduce the negative country-of-origin effects faced by developing countries. The research would have implications for location decisions in setting up global innovation/R&D activities.
urn:nbn:de:gbv:830-tubdok-11414
Keywords: 650